Biohybrid Nanoparticles to Negotiate with Biological Barriers. Issue 34 (28th June 2019) - Mohammadi, M. Rezaa; Corbo, Claudia; Molinaro, Roberto; Lakey, Jonathan R. T.
Abstract: Incapability of effective cross‐talk with biological environments has partly impaired the in vivo functionality of nanoparticles (NPs). Homing, biodistribution, and function of NPs could be engineered through regulating their interactions with in vivo niches. Inspired by communications in biological systems, endowing a "biological identity" to synthetic NPs is one approach to control their biodistribution, and immunonegotiation profiles. This synthetic‐biological combination is referred to as biohybrid NPs, which comprise both i) engineerable, readily producible, and trackable synthetic NPs as well as ii) biological moieties with the capability to cross‐talk with immunological barriers. Here, the latest understanding on the in vivo interactions of NPs, biological barriers they face, and emerging methods for quantitative measurements of NPs' biodistribution are reviewed. Some key biomolecules that have emerged as negotiators with the immune system in the context of cancer and autoimmunity, and their inspirations on biohybrid NPs are introduced. Critical design considerations for efficient cross‐talk between NPs and innate and adaptive immunity followed by hybridization methods are also discussed. Finally, clinical translation challenges and future perspectives regarding biohybrid NPs are discussed. Abstract : Novel manufacturing protocols have allowed for the synthesis of bio‐hybrid nanoparticles able to negotiate with immune system functionalities. This crosstalk has resulted important to overcome biological barriers, including the uptake and clearance of nanoparticles by the mononuclear phagocytic system and their off‐target accumulation. On the other hand, those protocols may favor their clinical translation.